An introduction to financial statement and cash flow analysis - Morse, Wayne J.; Davis, James R., 1936-; Hartgraves, Al L. (Cincinnati, Ohio : South-Western College, 1996)
This book is about: Financial statement analysis; Statement of csh flows; Glossary; ...
Keywords: Accounting; Finance; Cash management; Accounting; Cash flow; Cash management